The Appearance of Whale Sharks (Rhincodon typus) Based on Environmental Factors in Kwatisore Waters, Nabire Regency, Central Papua Province - Maruanaya, Yan (Journal Omni-Akuatika, 2024)
The appearance of whale sharks (Rhincodon typus) is related to the availability of food in a water area, and it has become a tourist attraction which requires integrated management to prevent it from becoming threats to whale sharks. The appearance of whale sharks is regular throughout the year with the highest number of individuals occurring only in Kwatisore waters. This study aims to examine the bio-ecology of whale sharks related to their appearance based on individuals, quantity, time of appearance, and sex. Primary data collection carried out from January 16 to March 26, 2023, using a census method on 4 units of fishing lift-net deployed in Kwatisore waters. The results showed that 21 individual whale sharks appeared with a total of 225 occurrences in January, 245 occurrences in February, and 248 occurrences in March. There was also one new individual that migrated into Kwatisore waters with the ID number 184. Whale shark appearances mostly happened in the morning and the appearance percentage was 100% male with a total length ranging from 3 to 7.5 m. Environmental factors in Kwatisore waters were in normal conditions supporting the appearance of whale sharks. Keywords: Whale sharks, appearance, new individual, environmental factors